APPLICATION OF THE PRINCIPLES IN SUTTANTA PITAKA TO DEVELOP THE ADMINISTRATION OF THE SANGHA - Thamathacho (Tuatuean), Phrakhru Dhammathorn Thawatchai; Phathong, Ketsada (Journal of MCU Nakhondhat, 2026)
This research article had three objectives: 1) To investigate the principles of Dhamma in the Suttanta Piṭaka related to the development of Sangha administration; 2) To examine the application of these principles to the development of Sangha administration; and 3) To propose guidelines for applying the principles of Dhamma in the Suttanta Piṭaka to improve Sangha administration. This study employed a qualitative research approach. Data were collected through in-depth interviews with 30 key informants and focus group discussions with 12 experts, all of whom were selected using purposive sampling. The research instrument consisted of a structured interview, while the data were analyzed through content analysis. The credibility of the findings was verified using triangulation techniques. The findings revealed that the key principles in the Suttanta Piṭaka applicable to the development of Sangha administration include the Aggañña Sutta, which explains the foundation of the legitimacy of authority; the Cakkavatti Sutta, which emphasizes moral leadership; and the Aparihāniyadhamma, which serves as a key mechanism for participatory organizational governance. These three principles can be integrated into a three-level Dhamma-based governance system comprising the policy, structural, and operational levels. The new body of knowledge derived from this study is the SIAD Sangha Governance Model, an integrated conceptual framework for enhancing Sangha administration through legitimacy, moral leadership, and participatory mechanisms. The model serves as a practical prototype for improving the administration of Sangha organizations as well as public organizations based on Buddhist principles. Furthermore, it can be applied as a comprehensive framework for developing effective Sangha administration in accordance with the principles of the Vinaya and the contemporary social context.